Health care waste materials changes under alkaline hydrolysis treatment - S. C. Pinho (2011)
In this work has been studied the behavior of some materials present in healthcare waste when treated by alkaline hydrolysis. The alkaline hydrolysis was performed with 0.1 M, 1 M or 2 M NaOH at 135 ºC. The efficiency of treatment was assessed by changes on the mass of the materials samples, and total organic carbon (TOC) and chemical oxygen demand (COD) in the effluent resulting from alkaline hydrolysis. Among the ten tested samples of materials, adhesive was the most degraded and showed the highest weight loss of 53.8 wt%. The final effluent obtained by alkaline treatment is hazardous due to its high pH, TOC and COD. The diaper and adhesive were the materials that released more TOC and COD to the resulting effluent. Those values were 17.3 and 45.9 g C/l and 42.0 and 143.76 g O2/l, respectively.